Positive postpartum wellbeing: What works for women - Daly, Deirdre; Hannon, Susan (My University, 2022)
Background: Women's experiences of pregnancy, birth and motherhood extend beyond healthcare provision and the immediate postpartum. Women's social, cultural and political environments shape the positive or negative effects of their experiences through this transition. However, there is limited research concerning the factors that women identify as being protective or promotive of maternal well‐being in the perinatal period and motherhood transition. Objective: To explore women's views on the factors within healthcare, social, cultural, organizational, environmental and political domains that do or can work well in creating positive perinatal experiences. Design, Setting and Participants: A qualitative descriptive study with embedded public and participant involvement (PPI). Participants were 24 women who were maternity care service users giving birth in Ireland. Results: Three themes were developed. The first theme, ‘tone of care’, related to women's interactions with and attitudes of healthcare professionals in setting the tone for the care they experienced. The second theme, ‘postpartum presence and support’, concerned the professional postpartum supports and services that women found beneficial in the motherhood transition. The final theme, ‘flexibility for new families’ addresses social and organizational issues around parents returning to paid employment. Discussion and Conclusion: Women suggested multiple avenues for promoting positive perinatal experiences for women giving birth in Ireland, which may be implemented at healthcare and policy levels. Women identified that maternal health education focuses on supporting informed decision‐making processes as a positive and worry‐alleviating resource. Additionally, women valued being met by healthcare professionals who regard women as the decision makers in their care experience. Exchanges in which healthcare professionals validate and encourage women in their mothering role and actively involve their partners as caregivers left lasting positive impressions. Extended and professional postpartum support was a common issue, and phone lines or drop‐in clinics were suggested as invaluable and affirming assets where women could access personalized support with healthcare professionals who had the knowledge and skills to genuinely approach women's concerns. Social and organizational considerations involved supporting parents to balance their responsibilities as new or growing families in the return to work. Public or Patient Contribution: Maternity care service users were involved in the interviews and manuscript preparation.
PUBLISHED
Keywords: maternal health; postnatal; postpartum period; qualitative research; salutogenesis; well‐being; Maternal Health; Maternal health care; Maternity Care; Postnatal care; Postpartum care; QUALITATIVE RESEARCH; Salutogenesis; maternity care research